A Techno-Economic Assessment of Steam Methane Reforming and Alkaline Water Electrolysis for Hydrogen Production - Ching Cheng Chu; Muhammad Danial Suhainin; Dk Nur Hayati Amali Pg Haji Omar Ali; Jia Yuan Lim; Poh Serng Swee; Jerick Yap Raymundo; Ryan Xin Han Tan; Mei Kei Yap; Hsin Fei Khoo; Hazwani Suhaimi; Pg Emeroylariffion Abas (Hydrogen, 2025)
This study explores hydrogen’s potential as a sustainable energy source for Brunei, given the nation’s reliance on fossil fuels and associated environmental concerns. Specifically, it evaluates two hydrogen production technologies; steam methane reforming (SMR) and alkaline water electrolysis (AWE), through a techno-economic framework that assesses life cycle cost (LCC), efficiency, scalability, and environmental impact. SMR, the most widely used technique, is cost-effective but carbon-intensive, producing considerable carbon dioxide emissions unless combined with carbon capture to yield “blue hydrogen”. On the other hand, AWE, particularly when powered by renewable energy, offers a cleaner alternative despite challenges in efficiency and cost. The assessment revealed that AWE has a significantly higher LCC than SMR, making AWE the more economically viable hydrogen production method in the long term. A sensitivity analysis was also conducted to determine the main cost factors affecting the LCC, providing insights into the long term viability of each technology from an operational and financial standpoint. AWE’s economic viability is mostly driven by the high electricity and feedstock costs, while SMR relies heavily on feedstock costs. However, Environmental Impact Analysis (EIA) indicates that AWE produces significantly higher carbon dioxide emissions than SMR, which emits approximately 9100 metric tons of carbon dioxide annually. Nevertheless, findings suggest that AWE remains the more sustainable option due to its higher LCC costs and compatibility with renewable energy, especially in regions with access to low-cost renewable electricity.